Hubungan Kualitas Tidur Dengan Glukosa Darah Sewaktu Pada Mahasiswa STIKes Kesetiakawanan Sosial Indonesia - Elgi Faninurafina; Yuri Pradika (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Sleep is a basic need required by everyone. One of the ways the body can function normally is by getting enough sleep. Student is a group that has quite a lot of activity so that it can affect sleep patterns. Sleep patterns can affect the blood glucose levels in the body. Blood glucose is the sugar found in the blood which is formed from the metabolism of carbohydrates. This study aims to see the relationship between sleep quality and blood glucose in Stikes Ketetiakawanan Sosial Indonesia students. This type of research is correlation research. The sample in this study were all students at Stikes Kesetiakawanan Sosial Indonesia using the purposive sampling technique. Based on the research results, it was found that 26 respondents (66.7%) had poor sleep quality and 34 respondents (87.2%) had normal glucose levels. The analysis using SPSS obtained a p value of 0.03 and a Correlation Coefficient value of 0.33, which shows that there is a positive correlation between sleep quality and blood glucose levels among students of STIKes Kesetiakawana Sosial Indonesia.